Financial Analysis and Business Development Strategy for Carp (Cyprinus carpio L) Floating Net at Pulau Harapan Village, Muara Muntai District - Cynthia Narulita; Helminuddin Helminuddin; Said Abdusysyahid (Jurnal Perikanan dan Kelautan, 2023)
The purpose of this study was to analyze the feasibility of the business, and business sensitivity, and develop strategies for the development of a floating net cage business in Pulau Harapan Village, Muara Muntai District. Data collection was carried out in April - August 2021, with a purposive sampling method with a total sample of 34 respondents consisting of 30 respondents of carp floating net cage business farmers and 4 stakeholder respondents. Data were analyzed using financial analysis with discounted investment criteria NPV, IRR, Net B/C R, and undiscounted investment criteria Payback Period, for sensitivity analysis and determining policy strategies using SWOT analysis. The results showed that the calculation of the score value was in quadrant 1 where the floating net cage (KJA) business in Pulau Harapan Village, Muara Muntai District was financially feasible (profitable) so that it could be continued (Go Project) and the results of the sensitivity analysis of the business were still in the profitable category and feasible to continue and the strategy used for the development of the floating net cage business was an Aggressive strategy